Globalization, domestic factors, and income inequality: evidence from Singapore and Angola - Wong, Benjamin Liang Min (Nanyang Technological University, 2022)
Contemporary literature today has had varying views on globalization's role in propagating and reducing income inequality. Based on the Stolper-Samuelson Theorem, globalization lowers income inequality in developing countries while increasing income inequality in developed countries. Other scholars argue that globalization serves as a catalyst for income inequality's propagation or that there are other domestic factors at play. This paper seeks to investigate the role of globalization on income inequality and whether it is the key determinant of the income distribution. Using panel data from 2014 to 2018 across 88 countries, the study employed a hierarchical fixed effect regression to explore the relationship between domestic factors and the Gini Index. It finds that globalization has a significant and negative impact on income inequality in the initial models. However, as other domestic factors were added, population growth rate, unemployment, and level of education were found to be the key factors affecting income inequality. These factors were then analyzed in the context of Singapore and Angola. The results showed that although there were some significant flaws in both countries, their problems were vastly different due to globalization-related factors.